Aged for Vengeance (A Tuscan Vineyard Cozy Mystery-Book 5) - Fiona, Grace (Lukeman Literary, 2021)
"Very entertaining. I highly recommend this book to the permanent library of any reader that appreciates a very well written mystery, with some twists and an intelligent plot. You will not be disappointed. Excellent way to spend a cold weekend!" --Books and Movie Reviews, Roberto Mattos (regarding Murder in the Manor) AGED FOR VENGEANCE (A TUSCAN VINEYARD COZY MYSTERY) is book #5 in a charming new cozy mystery series by #1 bestselling author Fiona Grace, author of Murder in the Manor (Book #1), a #1 Bestseller with over 100 five-star reviews-and a free download! Olivia Glass, 34, turns her back on her life as a high-powered executive in Chicago and relocates to Tuscany, determined to start a new, simpler life-and to grow her own vineyard. A high-end wine tour comes into town, led by a world-class museum. When they stop at the winery, it seems like the winery's big break-but when one of the tour members ends up dead, it jeopardizes everything. Can Olivia find the killer and save their reputation? Hilarious, packed with travel, food, wine, twists and turns, romance and her newfound animal friend-and centering around a baffling small-town murder that Olivia must solve-the TUSCAN VINEYARD is an un-putdownable mystery series that will keep you laughing late into the night. Book #6 in the series, AGED FOR ACRIMONY, is now also available!
Keywords: Krimi, detektivky